2002
DOI: 10.1212/wnl.58.3.428
|View full text |Cite
|
Sign up to set email alerts
|

Minicolumnar pathology in autism

Abstract: In autism, there are minicolumnar abnormalities in the frontal and temporal lobes of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
514
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 752 publications
(558 citation statements)
references
References 30 publications
35
514
0
6
Order By: Relevance
“…Instead, the improved tactile spatial localization that accompanies an increase in duration of adapting stimulation most likely would occur as a result of local dynamic corticocortical interactions that operate to improve the contrast of the primary somatosensory cortical response to a repetitive stimulus through lateral inhibition. Based on this perspective, the measures of tactile localization performance described in this paper appear to reflect the deficit in short-range parietal corticocortical connectivity identified in subjects with autism by Casanova and colleagues (Casanova et al, 2002(Casanova et al, , 2003. Such changes in connectivity could lead to the imbalance in excitation and inhibition that others have predicted underlies the neocortical hyperexcitability and unstable activity in cortical networks characteristic of autism (Polleux and Lauder, 2004;Rubenstein and Merzenich, 2003).…”
Section: Discussionmentioning
confidence: 70%
“…Instead, the improved tactile spatial localization that accompanies an increase in duration of adapting stimulation most likely would occur as a result of local dynamic corticocortical interactions that operate to improve the contrast of the primary somatosensory cortical response to a repetitive stimulus through lateral inhibition. Based on this perspective, the measures of tactile localization performance described in this paper appear to reflect the deficit in short-range parietal corticocortical connectivity identified in subjects with autism by Casanova and colleagues (Casanova et al, 2002(Casanova et al, , 2003. Such changes in connectivity could lead to the imbalance in excitation and inhibition that others have predicted underlies the neocortical hyperexcitability and unstable activity in cortical networks characteristic of autism (Polleux and Lauder, 2004;Rubenstein and Merzenich, 2003).…”
Section: Discussionmentioning
confidence: 70%
“…43 Cell columns are more numerous in the brains of autistic patients, and are smaller and less compact in their cellular configuration in BA9 of the DLPFC. 44 Functional magnetic resonance imaging has shown that these prefrontal structures are associated with impaired executive functioning, relating to working memory and attention in particular. 45,46 Diffusion tensor imaging has demonstrated differences in long-distance frontoparietal connections between autistic subjects and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Casanova et al [21,22] showed that in postmortem brain tissues from individuals with autism, the frontal and temporal cortical minicolumns were smaller, more numerous and less compact than those of non-autistic subjects. Alterations in the size and cellular distribution within cortical minicolumns in autism may reflect disturbances in the processing of thalamic inputs to cortex.…”
Section: Discussionmentioning
confidence: 99%
“…-stereotypical behaviors, impaired verbal and nonverbal communication and blunted social interaction) are accompanied by structural and functional changes in cortex, cerebellum and amygdala [3,4,7,8,[19][20][21][22]37,38,49,55,67,101,125]. Structural and functional changes apparent in early childhood suggest that autism is a disorder of brain development [4,19,20,[37][38][39]111].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation